Unlocking Safety Excellence: The Synergy of Leadership, Knowledge, and Motivation - Efi MiftahFaridl; Suyoto; Jovinda Percillia Marifatul Umairoh (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The study investigates the impact safety leadership, safety knowledge, and safety motivation on safety performance. Methodology: The study adopts a quantitative approach. The population comprises 237 employees of PT Paiton PLTU Probolinggo, with the entire population included in the sample using a combination of total sampling and non-probability sampling techniques. Partial least squares analysis was employed to analyze the data. Findings: The analysis reveals that safety leadership, safety knowledge, and safety motivation each have a positive and substantial impact on safety performance. This conclusion was drawn from calculations at a 5% significance level. Implications/Novel Contribution: This study provides valuable insights for organizations, emphasizing the importance of leadership development and continuous improvement in safety knowledge to cultivate a motivated workforce. These efforts are key to reducing workplace risks and enhancing overall safety performance, strengthening an organization’s safety culture.